(untitled) (Biological Sciences - PJSIR, 2008)
The study on contamination of well waters of Hyderabad city with arsenic and its effect on urine, hair and nails of people consuming this water revealed the concentration of arsenic in well waters to be 25.413 to 1286.47 ppb and that in urine of the people to be 2.032-33.906 ppb, in hair 105.7-427.96 ppb and in nails 8.579-71.033 ppb.